Memory and Teaching - Jatautaitė, Dileta (Acta Paedagogica Vilnensia, 2000)
The present work indicates that changes in the study of memory continue at a rapid rate, perhaps exponentially, but the basic structure of human memory is always constant. We know that memory actually is not an entity at all, but rather an aspect of the functioning of a complex information processing system. Items of information – words, propositions are fed into the system and, in a sense, are later retrieved. However, we have no reason to think that between input and output the words or propositions are stored in specific locations somewhere in the head. What is inside the head is a fabulous conglomeration of interconnected nerve cells. And that means that memorial processes can be studied and perfected (for example, in achieving the quickest way of learning languages). This assumption lies behind all experimental work on memory since it was initiated by Ebbinghaus. This work deals with the concerns of studies of memory throughout the history of its experimental study, the methods which have been used in experimentation and how they have altered as the decades have passed